2017
DOI: 10.1002/elan.201700398
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐based Electrochemical Devices Coupled to External Graphene‐Cu Nanoparticles Modified Solid Electrode through Meniscus Configuration and their Use in Biological Analysis

Abstract: This paper demonstrates, for the first time, the use of paper‐based electrochemical devices coupled to external solid working electrodes. The paper‐based electrochemical cells were fabricated using inexpensive and largely available office paper, according to a simple protocol that consists on the creation of hydrophobic barriers using paraffinized paper and preheated metal stamp. The counter and reference electrodes were integrated to the paper platform through the deposition of carbon and silver inks, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…LODs ranged from 0.5–2.5 μM. There is another work in which an ePAD sensor is developed for paracetamol and caffeine determination in urine samples using DPV . The originality of this paper relies on the fact that the working electrode is not integrated in the ePAD.…”
Section: Ed Based On Nanomaterials In Paper‐based Microfluidicsmentioning
confidence: 99%
“…LODs ranged from 0.5–2.5 μM. There is another work in which an ePAD sensor is developed for paracetamol and caffeine determination in urine samples using DPV . The originality of this paper relies on the fact that the working electrode is not integrated in the ePAD.…”
Section: Ed Based On Nanomaterials In Paper‐based Microfluidicsmentioning
confidence: 99%
“…Studies have shown that the detection performance of colorimetric methods can be improved by inducing the aggregation of nanomaterials in order to enhance the detection resolution [119,149,156]. Similarly, in the EC and SERS methods, the detection performance can be improved by patterning nanomaterials with good electrical conductivity on the electrode surface [120,125,135,166,167]. In CL and fluorescence methods, the intensity of the detection signal can be amplified through the catalytic reaction of nanomaterials and the induced fluorescence quenching [132,[168][169][170], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, "prohibited drugs" are psychotropic or narcotic drugs that are used for recreational "non-medical purposes" and may cause dependency and eventual addiction. Many lab-on-paper platforms have been proposed for the detection of drugs such as caffeine, paracetamol, adenosine, cocaine, ketamine, cannabidiol (CBD), methamphetamine (MA), 3,4-methylenedioxy -N-methamphetamine (MDMA) and tricyclic antidepressants [135][136][137][138][139][140][141][142]. Petroni et al [135] demonstrated a lab-on-paper platform with a CE sensor coupled to an external graphene-Cu nanoparticlemodified solid electrode through a meniscus configuration for the detection of paracetamol and caffeine in urine samples.…”
Section: Drugs and Ion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor was effective for the simultaneous detection of these analytes, with a detection limit for caffeine of 5.5 × 10 −8 mol L −1 . Lucca and coworkers [62] reported the first example of a paper-based electrochemical sensor for the simultaneous detection of caffeine and paracetamol in real biological samples. In particular, a chemically treated office paper coupled with two electrodes acted as an “electrochemical paper analytical device (ePAD)”, which allowed the reduction of the analyzed volume to the order of μL.…”
Section: Reduced Graphene Oxide (Rgo) and Electrochemically Reducementioning
confidence: 99%